(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article is devoted to the historical development of volleyball in Uzbekistan. It follows the journey of the sport from its introduction to the present day, highlighting the main stages, challenges and opportunities that shaped its growth. Through a comprehensive review of the literature, analysis of the methods used and study of the results, this article provides an understanding of the state of volleyball in Uzbekistan, discusses the factors affecting its development, provides conclusions and suggestions for its further development.